Optimización del tiempo y temperatura de secado convectivo en el contenido de capsaicinoides y capacidad antioxidante de harina de rocoto (Capsicum pubescens) - Peña Joaquin, Vicente Santos (2023)
The objective of this work was to investigate the optimization of time (10 – 24 hours) and temperature (50 – 80 °C) of convective drying in the conservation of capsaicinoids and antioxidant capacity of rocoto flour (Capsicum pubescens). For this, the hot pepper samples (red, yellow and green) were treated according to a DCCR design with 11 treatments. The results showed an initial concentration of capsaicinoids of 12.24, 19.64 and 15.32 mg/100 g for the red, yellow and green varieties, respectively. The initial antioxidant capacity, measured by DPPH, was 71.28, 84.21 and 79.87%, respectively. The drying process showed that by increasing the temperature and drying time, both the capsaicinoids and the antioxidant capacity decrease. In this sense, the concentration of capsaicinoids had the maximum decrease to 4.28, 6.93 and 5.89 mg/100 g in the red, yellow and green varieties, respectively. Similarly, the antioxidant capacity decreased to 66.66, 80.47 and 75.45%, respectively. It was also determined that the optimal drying conditions in the three varieties of rocoto, vary between 57.5 - 67.5 °C with times between 11.2 – 15.5 hours. The effect of temperature and time in a linear, quadratic and interacted manner exerted a statistically significant effect (p < 0.05) on the dependent variables.